Karakteristik histologi perkembangan folikel ovariumfase luteal pada kancil (Tragulus javanicus) - Hamny .; S. Agungpriyono .; I. Djuwita .; W.E. Prasetyaningtyas .; I.Nasution . (Hemera Zoa, 2010)
The lesser mouse-deer (Tragulus javanicus) is one of the Indonesia biodiversity. This animal distributes only in South-East Asia and Hindia. The lesser mouse-deer is the smallest ungulate in the world and regarded as an ideal model to biomedic and ruminant research. As their population becoming extincted, conservation efSort is very important. One of the eflorts in supporting the lesser mouse-deer conservation is by improving our knowledge reproductive physiology of the female lesser mouse-deer. The aim of this study was to investigate the histological characteristic of ovarian follicles development of the female lesser mouse-deer. Experiment was done on the ovary (n=4). The ovary was fixed in Bouin solution andprocessed according to standard of histology. The slides were stained in HE. At luteal phase, the developing follicles can be classified into 10 stages. The number of developing follicles in the left ovary were higher then in the right.